2011
DOI: 10.1002/dev.20566
|View full text |Cite
|
Sign up to set email alerts
|

Organizational effects of oxytocin on serotonin innervation

Abstract: Oxytocin (OT) has an organizational effect within the central nervous system and can have long-lasting effects on the expression of social behavior. OT has recently been implicated in modulating the release of serotonin through activation of receptors in the raphe nuclei. Here we test the hypothesis that OT can have an organizational effect on the serotonergic system. Male prairie voles received an intraperitoneal injection on postnatal day 1 with 3.0 or .3 µg OT, an OT antagonist, or a saline control. Brains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
1
42
0
1
Order By: Relevance
“…In women, OT increases the VTA activation to salient sexual and infant stimuli (Gregory et al 2015) in nulliparous and postpartum women, respectively. Finally, the raphe magnus shows a specific OT-ir innervation, from which OT can act on serotoninergic neurons (Eaton et al 2012;Mottolese et al 2014) modulating anxiety (Yoshida et al 2009) and aggression (Pagani et al 2015).…”
Section: Distribution Of Ot-immunoreactive Processesmentioning
confidence: 99%
“…In women, OT increases the VTA activation to salient sexual and infant stimuli (Gregory et al 2015) in nulliparous and postpartum women, respectively. Finally, the raphe magnus shows a specific OT-ir innervation, from which OT can act on serotoninergic neurons (Eaton et al 2012;Mottolese et al 2014) modulating anxiety (Yoshida et al 2009) and aggression (Pagani et al 2015).…”
Section: Distribution Of Ot-immunoreactive Processesmentioning
confidence: 99%
“…Importantly, in the raphe nuclei, the core area of 5-HT synthesis, serotonergic neurons display OXT receptors and OXT modulates the release of 5-HT (9). Recent results have also shown that administration of OXT during the postnatal period increases the length of serotonergic axons in the hypothalamus and in the amygdala (10). In return, 5-HT is able to modulate OXT release while interacting with different 5-HT receptors in the hypothalamus (11).…”
mentioning
confidence: 89%
“…The role of dopamine, serotonin, and opioid systems should also be investigated because these neurotransmitters are involved in the rewarding properties of alcohol and other drugs, and play a role in vole social behavior as well, including through interactions with the oxytocin system (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%